Occurrence of Aflatoxin M1 in Raw Milk Marketed in Italy: Exposure Assessment and Risk Characterization - Serraino, Andrea; Bonilauri, Paolo; Kerekes, Kata; Farkas, Zsuzsa; Giacometti, Federica; Canever, Alessandra; Zambrini, Angelo Vittorio; Ambrus, Árpád (Frontiers in Microbiology, 2019)
The current study is based on the AFM1 contamination of milk, determined from April 2013 to December 2018 in the framework of a self-control plan of 6 milk processing plants in Italy. These data – together with the consumption data of milk consumers – were evaluated and used for the calculation of the Estimated Daily Intake (EDI), the Hazard Index (HI) and the fraction of hepatocarcinoma cases (HCC) due to AFM1 exposure in different population groups. Altogether a total of 31,702 milk samples were analyzed, representing 556,413 tons of milk, which is an outstanding amount compared to published studies. The results indicate the monthly fluctuation of AFM1 levels through a period of nearly 6 years. The EDI of AFM1 in different population groups were in the range of 0.025-0.328 ng kg-1 body weight (bw) per day, based on the average consumption levels and weighted mean contamination of the milk in the study period. Considering average consumptions, in the groups of infants and toddlers, the HI calculation resulted in 1.64 and 1.4 respectively, while for older age groups it was <1. The estimated fractions of HCC incidences attributable to the AFM1 intakes were 0.005 and 0.004 cases per 100,000 individuals in the 0-0.9 and 1-2.9-years age groups respectively and below 0.004 cases in the other age categories. The monthly average AFM1 contamination of tested milk consignments ranged between 7.19 ng kg-1 and 22.53 ng kg-1. Although, the results of this extensive investigation showed a low risk of HCC, the variability of climatic conditions throughout years that influence AFB1 contamination of feed and consequently AFM1 contamination of milk, justifies their continuous monitoring and update of the risk assessment.